A case of osteofibroma on the symphysis mandible in a cow - YAYLA, S; KILIÇ, E; ÖZEN, H; DAĞ, S; BARAN, V; AYDIN, U (Journal of the Hellenic Veterinary Medical Society, 2018)
Osteofibroma or ossifying fibroma both in human and animals is a rarely seen benign neoplasia. It usually locates on the mandible. Although it is commonly seen in young horses no case reports were described in cattle. In this case report, an osteofibroma located at the symphysis mandible in a cow was described. The tumor mass was reported to grow over in a two-month period to the size of soccer ball. The mass was totally extirpated and histopathological examination was performed. The mass was diagnosed as osteofibroma in microscopic examination.